Oddziaływanie bezpośrednich inwestycji zagranicznych na kształtowanie środowiska ekonomicznego Polski - aspekty teoretyczne - Nowak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the article, the author makes a survey concerning the Foreign Direct Investment influence on the Polish national economy. The paper presents micro- and macro-scale approaches to this problem. The author also indicates positive and negative effects of FDI on the economy. The author focuses on correlation between aspirations and expected goals. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 386-393